WHAT ARE THE BARRIERS IN PARENTS INVOLVEMENT AND PARENT TEACHER COLLABORATION? - Kaur, Jaswinder (International Journal of Psychosocial Rehabilitation, 2021)
As a parent, you show your commitment to your children’s education by giving them resources and time. A study by Fan, Li, and Sandoval (2018) found six categories of parental involvement: Making it easier for parents and teachers to communicate will help students and the school as a whole, but it will also help parents and students themselves, as involuntary participation in school decision-making and collaboration with other stakeholders (like students and teachers) to make improvements to the school itself will help both. There are two types of parental involvement: home-based and school-based parental involvement.